Removal of Organic Pollutant from Industrial Rubber Wastewater Using Pineapple Crown Bio-Adsorbents - Riska Rahmah Dani Fitria; Anggrika Riyanti; Hadrah; Marhadi; Nazarudin; Sisca Afrilia Silalahi (Magister Program of Material Science, Graduate School of Universitas Sriwijaya, 2026)
Industrial rubber wastewater contains high levels of organic substances (proteins, carotenoids, organic salts, and lipids in residual latex) that can be observed in high concentrations of BOD5 (Biochemical Oxygen Demand) and COD (Chemical Oxygen Demand). Pineapple waste is an organic waste that can be utilized as a bio-adsorbent to remove pollutants from wastewater. This study aims to investigate the effectiveness of pineapple crown waste activated with KOH in removing BOD5 and COD in rubber industry wastewater. The effectiveness of the adsorbent was tested in batches at varying adsorbent dosages of 0.5 g, 1.0 g, and 1.5 g at stirring speeds of 50 rpm, 100 rpm, and 150 rpm. The adsorption isotherm model was analyzed using the Langmuir and the Freundlich models. The results showed that the optimum BOD5 removal rate in rubber industry wastewater using pineapple crown adsorbent was achieved at an adsorbent dosage of 0.5 g with a stirring speed of 100 rpm, resulting in an adsorption capacity of 62.78 mg/g and a removal efficiency of 94.35%. The optimum COD removal was achieved at an adsorbent dosage of 0.5 g, with a stirring speed of 100 rpm, resulting in an adsorption capacity of 199.816 mg/g and a removal efficiency of 95.15%. The adsorption isotherm model most suitable for both BOD5 and COD is the Freundlich model. Increasing the adsorbent dosage does not significantly enhance removal efficiency.